An Exploration of Holistic and Soulful Perspectives on Adult Education and Lifelong Learning: A Dialogue in Indigenous Western Australia - Colleen Kawalilak (Adult Education Research Conference, 2004)
This research, an autoethnography of an adult educator’s journey in Indigenous Western Australia, explored how ‘meaningful dialogue’ transformed’ perspectives on adult education and lifelong learning. Four specific concepts evolved from the data: the power of story; an equality of difference; the significance of space; and the experience of oneness.